Role of Pakistan poverty alleviation fund's micro credit in poverty alleviation: a case of Pakistan - Shirazi, Nasim Shah; Khan, Aman Ullah (2009)
Poverty alleviation has been one of the major agenda of all civilized societies throughout the history. Different strategies have been adopted in Pakistan for the purpose, which include special programs and short-term measures targeted towards improving the earning capacity of masses and provision of social safety nets for the really poor. With a view to enhance the access of the low-income communities to socio-economic services, the Government of Pakistan has set up an independent and professionally managed unit, the Pakistan Poverty Alleviation Fund (PPAF). The Fund is working through a network of partner organizations having strong community outreach programs. PPAF continuously monitors and analyzes effectiveness of its programs. This paper attempts to quantify the impact of PPAF micro credit on poverty alleviation.. Data collected in Gallup (2005) has been utilized for the purpose. Counter-factual ‘Combined approach’ has been employed in the analysis. The Paper concludes that Micro credit has reduced poverty by 3.05 percentage points in the period under study